ANALISIS PENGELOLAAN HUTANG SEBAGAI ALAT UNTUK MENINGKATKAN PROFITABILITAS PADA PT. PERKEBUNAN NUSANTARA V PEKANBARU - Tasya Nadira Putry; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Good debt management will determine whether or not the company's activities. This study aims to determine and analyze the effectiveness of debt management as a tool to increase the profitability of PT. Nusantara V Pekanbaru Plantation. In this study using quantitative descriptive data types. Sources of data used are primary data obtained through interviews and secondary data using financial statement data from PT. Perkebunan Nusantara V Pekanbaru period 2016-2020, and using ratio analysis.            The results of research on debt management as a tool to increase profitability at PT. Perkebunan Nusantara V Pekanbaru shows that debt management in increasing profitability is not good. This is because in 2016-2020 all debt management as measured by the solvency ratio and profitability is still fluctuating. Keywords: Debt Management and Profitability